Menyelusuri kearifan budaya Suku Osing warisan tradisi dan keunikan identitas lokal - Dwi Indah Lestari; Kurnia, Heri; Khasanah, Isrofiah Laela (Jurnal Ilmu Sosial dan Budaya Indonesia, 2023)
In the background context, the Osing Tribe, an ethnic group in East Java, Indonesia, has been a custodian of rich cultural wisdom. This article explores important aspects of Osing life and identity, focusing on history, cultural values, traditions, and preservation challenges. Through a literature review approach, we gather and analyze various relevant sources to highlight the uniqueness of Osing culture and their preservation efforts. From ritual traditions to belief systems, we find that the Osing exhibit a close relationship between humans, nature, and spirituality in their daily lives. Despite facing pressures from globalization and modernization, Osing cultural preservation efforts continue through local community initiatives and external support. Our conclusion emphasizes the importance of appreciation and support for the sustainability of Osing culture as an integral part of Indonesia's cultural wealth. Thus, the article underscores the need to preserve and understand the valuable heritage of the Osing tribe for a sustainable future.